Exploring the Multifaceted Roles of Non-Native English-Speaking Teachers (NNEST) in Enhancing participants' Speaking Proficiency - Gusti Milla Milla Quaidy; Zamratul Khairani; Ernest Isakov; Abdurrahman Kalambekov (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study explores the roles of Non-Native English Speaking Teachers (NNESTs) in facilitating the improvement of participants' English speaking skills. The research was prompted by the challenge faced by a NNESTs from Indonesia, who relocated to Kyrgyzstan to teach English as a second language. The teacher lacked cultural knowledge to support his participants' language learning. To address this, the study employed a descriptive qualitative research design and utilized interviews as the primary data collection method to investigate how NNESTs support the development of their participants' English speaking ability. The analysis employed a Miles and Huberman data analysis to identify patterns and themes in the data. The findings reveal that NNESTs design instructional approaches that foster an environment conducive to speaking practice and enable participants to engage in conversation without fear of criticism. Additionally, the teachers provide personalized feedback to help participants identify their areas of weakness. Creating an engaging learning environment encourages participants to use English more frequently.